Molecular Docking Studies: Hepatitis C Viral-RNA-Dependent RNA Polymerase (RdRp) Inhibitory Activity of Siddha Herbal Formulation Sittramutti khirutham (SK) - Elanchezhian, Medini; Ramasamy, Suresh; Balasubramani, Abarna; Chidambaram, Lakshmanaraj (Asian Journal of Biological and Life Sciences, 2025)
Background: Docking studies of Sittramutti khirutham (SK) compounds against HCV RdRp (PDB:3MWV) were performed to evaluate inhibitory potential. Results: Compounds such as Curcumin, Maslinic acid, Arjungenin, Andrograpanin, Andrographolide, and Epiafzelechin showed 2–3 interactions with active residues, indicating promising RdRp inhibition. Conclusion: Docking suggests SK compounds may inhibit HCV RdRp and warrant further pharmacological validation.
Keywords: Hepatitis C; Molecular docking; Siddha